TINDAK ILOKUSI PIDATO BASUKI TJAHAJA PURNAMA DI KEPULAUAN SERIBU, 27 SEPTEMBER 2016 Suatu Analisis Wacana - SIMANULLANG, NICK CARTER (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT Â Â This research specifically discusses the type and function of speech acts of illocution contained in the speech of Basuki Tjahaja Purnama in Kepulauan Seribu, September 27, 2016. The method used in this research is descriptive method by using the substitution technique and the lesap technique. From the results of this study, the authors found 4 types of acts of ilokusi, namely assertive, directive, expressive, and komisif contained in the speech. The author then analyzes these sentences by using the subterfuge technique and the substitute technique to determine the function of the illocution actions contained therein. The function of the act of illocution that the author finds in assertive speech acts is stated, suggested, and claimed. The function of the directive speech acts the author finds is to advise, order, and order. The expressive act of speech acts that the author finds is to blame. The commissive speech act function that the author finds is promising. Keywords : Illuminative, Assertive, Directive, Expressive, Commissive.